Siderophore-producing rhizobacteria as a promising tool for empowering plants to cope with iron limitation in saline soils: a review - Ferreira, Maria J. (2019)
Iron (Fe) bioavailability to plants is reduced in saline soils; however, the exact mechanisms underlying this effect are not yet completely understood. Siderophore-expressing rhizobacteria may represent a promising alternative to chemical fertilizers by simultaneously tackling salt-stress effects and Fe limitation in saline soils. In addition to draught, plants growing in arid soils face two other major challenges: high salinity and Fe deficiency. Salinity attenuates growth, affects plant physiology, and causes nutrient imbalance, which is, in fact, one of the major consequences of saline stress. Iron is a micronutrient essential for plant development, and it is required by several metalloenzymes involved in photosynthesis and respiration. Iron deficiency is associated with chlorosis and low crop productivity. The role of microbial siderophores in Fe supply to plants and the effect of plant growth-promoting rhizobacteria (PGPR) on the mitigation of saline stress in crop culture are well documented. However, the dual effect of siderophore-producing PGPR, both on salt stress and Fe limitation, is still poorly explored. This review provides a critical overview of the combined effects of Fe limitation and soil salinization as challenges to modern agriculture and intends to summarize some indirect evidence that argues in favour of siderophore-producing PGPR as biofertilization agents in salinized soils. Recent developments and future perspectives on the use of PGPR are discussed as clues to sustainable agricultural practices in the context of present and future climate change scenarios.